Fiscal Sociology and the Theory of Public Finance. An Exploratory Essay (an excerpt) - Richard E. Wagner (Journal of Economic Sociology, 2016)
This book presents an alternative approach to public finance, which supposedly refers to general social theory. This approach contrasts with the perspective that regards state and economy as autonomous and independent spheres. According to Richard Wagner, “government” refers to a set of spaces where social interactions proceed and unfold. Fiscal activities should be associated less with state intervention in the economy than with arenas for cooperation and conflicts. The author stresses the importance of emergent processes of development driven by conflicts between people and their plans. Wagner points out that this book presents his personal view on the theory of public finance and hopes that it will attract a wide audience.The Journal of Economic Sociology is publishing the first chapter, “Contrasting Architectonics for a Theory of Public Finance.” In the first chapter, Wagner discusses two contrasting approaches to public finance: the predominant and alternative approaches. The former treats finance as a part of economic system. The latter treats it as a form of social theorizing. The author supposes that a dialog between these two approaches is necessary.